Structural dependence of the microwave dielectric properties of Cr³⁺-substituted ZnGa₂O₄ spinel ceramics : crystal distortion and vibration mode studies - Lu, Xiaochi (2021)
Zn[CrGa(₁-ⅹ)]₂O₄ (abbreviated Cr-ZGO) ceramics with x = 0–0.15 were synthesized by the conventional solid state method. The correlation between the microwave dielectric properties and the changes in the crystal structure and cation distribution of Cr-ZGO as a function of Cr³⁺ substitution for Ga3+ has been systematically investigated. The addition of Cr³⁺ promotes the densification of the ceramics and results in a normal spinel structure with Cr³⁺ occupying an octahedral site. With an increase in the Cr3+ content from 0 to 15 mol%, the er of the ceramics increases, while the tf remains almost unchanged and the Q f values ramp up to a maximum at 1 mol% Cr³⁺ addition and then ramp down continuously. 1Cr-ZGO exhibits the best microwave dielectric properties, with er, Q f, tand and tf being 9.88 (@9.9 GHz), 111 470 GHz, 8.87, and 74 ppm ⁰C-¹ , respectively. The Q f value was increased by almost 40% compared with the pure ZGO ceramics (B80 000 GHz). The enhancement of er and Q f values of Cr-ZGO can be attributed to the better bulk density, but further analysis by Rietveld refinement, Raman spectroscopy and FT-IR spectroscopy elucidated that the octahedral tilting in the spinel structure and the degree of short-range cation distribution are other governing factors. The effect of Cr³⁺ substitution for Ga³⁺ on the octahedral distortion and cation distribution in the spinel structure has been discussed in detail.